EVALUATION OF THE AQUACROP MODEL PERFORMANCE AND THE IMPACT OF FUTURE CLIMATE CHANGES ON POTATO PRODUCTION UNDER DIFFERENT SOIL MANAGEMENT SYSTEMS - A. A. A. A. Al-Lami,; S. S. Al-Rawi,; A. S. Ati, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate the effect of surface sprinkler and drip irrigation systems using a model AquaCrop, irrigation intervals, bio-organic fertilizers and polymers in desert soils. Two field experiments were conducted during the spring season 2020 at Karbala governorate. The experiment included three factors: 1-Irrigation system surface drip T1 and sprinkler T2, 2- The Irrigation interval: every 2 days I1, 4 days I2 and 6 days I3, 3- Addition of soil conditioners: control without any addition C, bio-organic fertilizers (seek) B, polymer (zeba) P, and polymer+ bio-organic fertilizers P+B. The experiment was designed according to the nested design with three replicates results of regional climate models and AquaCrop model. The results showed that there was an increase in the amount of annual precipitation and seasonal during the periods (2016-2035) and (2046-2065) under RCP4.5 scenario, compared to the base period (1985-2005). With an increase in the amount of annual precipitation and seasonal during the period at scenario RCP8.5 with a slight decrease during the period (2046-2065) compared to the base period. Moreover, an increase in the maximum and minimum temperatures according to scenario RCP4.5 and RCP8.5 scenario during the period (2016-2035) and (2046-2065) compared to the base period. The expected productivity using the AquaCrop, as R2 was 0.85 and 0.81 for twelve years, under surface drip irrigation systems and sprinkler, respectively. The correlation coefficient (r) was 0.95 and 0.90, the root means square error (RMSE) 2.43 and 2.19, and the efficiency coefficient 0.66 and 0.42 for the surface drip and sprinkler systems, respectively. Finally, the increase in water productivity and productivity in the scenario RCP4.5 and RCP8.5 for the treatment of BP and the irrigation interval I1and treatment C and the irrigation interval I3 when comparing the base period with the periods (2016-2035) and (2046-2065) For surface drip irrigation systems and sprinkler.